2016
DOI: 10.1038/onc.2016.44
|View full text |Cite
|
Sign up to set email alerts
|

The heparan sulfate sulfotransferase 3-OST3A (HS3ST3A) is a novel tumor regulator and a prognostic marker in breast cancer

Abstract: The heparan sulfate sulfotransferase 3-OST3A (HS3ST3A) is a novel tumor regulator and a prognostic marker in breast cancer Mao, X.; Gauche, C.; Coughtrie, M. W. H.; Bui, C.; Gulberti, S.; Merhi-Soussi, F. Citation for published version (APA):Mao, X., Gauche, C., Coughtrie, M. W. H., Bui, C., Gulberti, S., Merhi-Soussi, F., ... Fournel-Gigleux, S. (2016). The heparan sulfate sulfotransferase 3-OST3A (HS3ST3A) is a novel tumor regulator and a prognostic marker in breast cancer. Oncogene, 35, 5043-5055. DOI: 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Hyper-methylation of the genes encoding HS3ST2 and HS3ST3A was described in a number of cancer cells. Reversing methylation restored the expression of theses isozymes and resulted in the suppression of tumor cell growth, suggesting anti-oncogenic properties [ 15 , 16 , 17 , 18 ]. Conversely, we and others demonstrated that forced expression of HS3ST2 resulted in increased proliferation and viability of MDA-MB-231 cells [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyper-methylation of the genes encoding HS3ST2 and HS3ST3A was described in a number of cancer cells. Reversing methylation restored the expression of theses isozymes and resulted in the suppression of tumor cell growth, suggesting anti-oncogenic properties [ 15 , 16 , 17 , 18 ]. Conversely, we and others demonstrated that forced expression of HS3ST2 resulted in increased proliferation and viability of MDA-MB-231 cells [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that conflicting literature reported that certain HS3STs may act as either anti-oncogenic or tumor-promoting regulators. On the one hand, aberrant methylation of the genes encoding HS3ST2 and HS3ST3A was described in various cancers and tumor cells, and reversing methylation restored their expression and resulted in the suppression of tumor cell growth [ 15 , 16 , 17 , 18 ]. On the other hand, HS3ST2, 3B and 4 were reported to promote cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, EXT1 was found to be elevated in plasma of human cholangiocarcinoma patients and proposed to be the prognostic marker for cholangiocarcinoma [52]. Genetic loss of NDST4 in colorectal cancer [53] and high HS 3-O-sulphotransferase 3A expression in HER2-positive breast cancer patients [11] were shown to be associated with poor prognosis. Other studies have investigated how changes in HS biosynthetic enzyme expression levels influence growth factor responses in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Filoviruses, including Ebola virus (EBOV) and Marburg virus (MARV), known to cause hemorrhagic fever with a high mortality rate are also known to use cell surface HS and enzyme EXT-1 involved in HS-biosynthesis (Riblett et al, 2016 ). In addition, Rift Valley fever virus (RVFV), also an emerging pathogen that can cause lethal hemorrhagic fever syndrome in humans, has been documented to use HS during the initial stages of infection (Mao et al, 2016 ).…”
Section: Heparan Sulfate- a Gateway For The Emerging Diseasesmentioning
confidence: 99%